1984
DOI: 10.1073/pnas.81.23.7656
|View full text |Cite
|
Sign up to set email alerts
|

A ligand-specific action of chelated copper on hypothalamic neurons: stimulation of the release of luteinizing hormone-releasing hormone from median eminence explants.

Abstract: We have previously shown that chelated copper stimulates the release of luteinizing hormone-releasing hormone (LHRH) from isolated hypothalamic granules. In this study, we wished to ascertain if chelated copper acts on hypothalamic neurons to stimulate LHRH release and, if so, what is the ligand specificity of this interaction. An in vitro system of explants of the median eminence area (MEA) was established and characterized. MEA explants were exposed for 15 muin to 50 /uM copper, and then they were incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Those workers reported that dairy cows fed a mineral (Cu, Zn, and Mn) proteinate had a reduced incidence of cystic ovaries and days to first estrus. In rats, a Cu-histidine complex stimulates LHRH release from hypothalamic neurons (Barnea and Colombani-Vidal 1984;Barnea et al 1986). Swine studies have shown that LHRH raises LH secretion [see the review by Estienne et al (1997)] and that higher LH secretion before weaning is associated with an early return to estrus in postweaning sows (Shaw and Foxcroft 1985;King and Martin 1989;Tokach et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those workers reported that dairy cows fed a mineral (Cu, Zn, and Mn) proteinate had a reduced incidence of cystic ovaries and days to first estrus. In rats, a Cu-histidine complex stimulates LHRH release from hypothalamic neurons (Barnea and Colombani-Vidal 1984;Barnea et al 1986). Swine studies have shown that LHRH raises LH secretion [see the review by Estienne et al (1997)] and that higher LH secretion before weaning is associated with an early return to estrus in postweaning sows (Shaw and Foxcroft 1985;King and Martin 1989;Tokach et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…A higher level of luteinizing hormone (LH) before weaning was associated with a shorter weaning-to-estrus interval in sows (Shaw and Foxcroft 1985;King and Martin 1989;Tokach et al 1992). Copper-histidine complex stimulates the release of luteinizing hormone-releasing hormone (LHRH) from hypothalamic neurons in rats (Barnea and Colombani-Vidal 1984;Barnea et al 1986) and maybe in pigs. The mineral proteinates used by Spears and Flowers (1995) included a CuP containing 10% copper and 1% histidine.…”
mentioning
confidence: 99%
“…In vitro incubations o f the MEA explants were carried out as pre viously described in detail [7,11]. Briefly, explants (1 MEA/0.6 ml KRP) were incubated at 37 °C under air.…”
Section: In Vitro Incubationsmentioning
confidence: 99%
“…We have previously established that after the 30 min equilibration period, LHRH release from nonstimulated tissue pro ceeds at a constant rate for at least 2 h [ 11 ] and that when MEA are treated with Cu and PGE2, maximal rate of LHRH release is manifested within the 15-min period o f PGE2 exposure [3,6,7). This time course of Cu/P G E t stimulation of LHRH release was reconfirmed in this study using MEA of intact, ovariectomized, and ovariectomized-estrogentreated rats.…”
Section: In Vitro Incubationsmentioning
confidence: 99%
“…Using explants of the median eminence area (MEA) [4] or LHRH secretory granules isolated from the MEA [2,6,26,27] incubated under in vitro conditions, we have demon strated that extracellular chelated copper can lead to LHRH release from LHRH neuronal terminals and that one site of action of chelated copper is the secretory granule itself. Our observation of a strict ligand specificity for the action of chelated copper at both the level of the axonal terminal and the secretory granule is suggestive that copper interacts with specific sites present on these cellular com partments.…”
mentioning
confidence: 99%